Development of sputtered Nb3Sn films on copper substrates for superconducting radiofrequency applications. (21st January 2019) - Ilyina, E A; Rosaz, G; Descarrega, J B; Vollenberg, W; Lunt, A J G; Leaux, F; Calatroni, S; Venturini-Delsolaro, W; Taborelli, M
Abstract: Superconducting radiofrequency (SRF) cavities that could provide a higher quality factor as well as a higher operational accelerating gradient at an affordable cost are in high demand for the future generation of particle accelerators. This study aims to demonstrate the potential of Nb3 Sn as material of choice for such SRF applications. Due to its brittle nature, the only way to produce an Nb3 Sn SFR cavity is to synthesise a thin layer inside a cavity made of niobium or copper. In this work, direct current magnetron sputtering using a stoichiometric target of Nb3 Sn was employed to produce films on copper samples. Assessment of the morphology, microstructure and superconducting properties were performed in order to ensure that this approach is suitable for SRF applications. The potential of the method is proven by obtaining films, which exhibit a crack-free surface, dense morphology and critical temperatures ( T c ) up to 16 K. The essential properties of the films have also been investigated with respect to the deposition and annealing conditions. The use of krypton as working gas during deposition increases the atomic percent of Sn in the film compared to argon. However, in contrast to argon, higher krypton pressures reduce the atomic percent of Sn. It was also found that long-lasting high-temperature annealing leads to higher superconducting critical temperatures due to an increased crystallographic order. Particular attention was given to the influence of the copper substrate on the film growth as well as the microstructural and superconducting characteristics. We discuss the main constraints introduced by the copper substrate, such as copper interdiffusion during annealing, lattice mismatch and difference in thermal expansion coefficients and methods to overcome them.